Fatal case of hemolytic-uremic syndrome in an adult due to a rare serogroup O91 Entero hemorrhagic Escherichia coli associated with a Clostridium difficile infection. More than meets the eye. (August 2015) - Guillard, Thomas; Limelette, Anne; Le Magrex-Debar, Elisabeth; Wynckel, Alain; Gouali, Malika; Mariani-Kurkdjian, Patricia; Guyot-Colosio, Charlotte; de Champs, Christophe
Highlights: To our knowledge, O91 HUS cases are poorly reported in literature. We report here a case of post-diarrheal HUS due to EHEC O91 in an elderly patient in whom diagnosis was delayed given the C. difficile infection previously diagnosed. This case highlights the usefulness of Shiga-toxin detection. EHEC detection in children and adults with bloody diarrhea is a major public health issue because it will help to increase epidemiological knowledge about non-O157 infection and prophylactic and therapeutic management of severe complications such as HUS. Abstract: Hemolytic-uremic syndrome due to enterohemorrhagic Escherichia coli, belonging to serogroup O91 has rarely been described. We report here a case of post-diarrheal HUS due to EHEC O91 in an elderly patient for whom diagnosis was delayed given a previously diagnosed C. difficile infection. This case highlights the usefulness of Shiga-toxin detection.